Chronicle of the European case law on equality (from 1/9/2018 to 31/8/2019) - Jacqmain, Jean (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract. This paper deals with the analysis of judgments related to the principle of equal treatment and opportunities and delivered from September 1, 2018 until August 31, 2019 by the Court of Justice and General Court of the European Union. It also includes judgments and decisions on the subject during this period issued by the European Court of Human Rights